Extended storage of cold raw milk on yogurt manufacturing - Fagnani, Rafael; Schuck, Josiane; Botaro, Bruno Garcia; Santos, Fernando Cesar dos (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effect of the extended cold storage of raw milk on the kinetics of fermentation on yogurt production, as well as on the product’s microbiological and physicochemical properties during shelf life. Three treatments were evaluated: yogurts made with raw milk stored for 4, 72, and 168 hours. Kinetics of fermentation was assessed through the lactic acid production rate, growth rate of Streptococcus thermophilus and Lactobacillus bulgaricus, and time to reach pH 5.0 and 4.5. The physicochemical and microbiological characteristics of raw milk and yogurts were also analyzed during cold storage at 4°C. The microbial quality of raw milk was affected by the storage time of 168 hours, with a decreasing tendency in the mesophiles:psychrotrophs ratio. Extended storage of raw milk beyond 72 hours negatively affects yogurt production, despite the low initial bacterial count, decreasing lactic acid production, S. thermophilus growth rate, pH, and protein content. Therefore, to optimize fermentation and yogurt shelf life, the maximum storage time for raw milk at 4°C should not exceed 72 hours.